Efektivitas Media Google Sites untuk Meningkatkan Pembelajaran IPAS Bagi Anak Tunarungu - Fepiana, Indrika; Iswari, Mega; Nurhastuti, Nurhastuti; Zulmiyetri, Zulmiyetri; Yuliana, Syari (Indo-MathEdu Intellectuals Journal, 2024)
This research is motivated by the problem found in phase C, namely a deaf student who has difficulties in learning science and science in the material where living things live. This study aims to prove whether the use of google sites learning media is effective in improving the learning of deaf students in science and science subjects in the material where living things live in SLB Negeri 1 Pariaman. This study uses a type of experimental research in the form of Single Subjeck Research (SSR) with an A-B-A design. The subjects in this study are phase C deaf students at SLB Negeri 1 Pariaman. The data collection techniques in this study are observation and tests. The data was analyzed using qualitative and quantitative descriptive. The results of the study showed that in the baseline condition (A1) which was carried out three observations and obtained a stable percentage of 20%. In the intervention condition (B) which was carried out 5 times with a stable percentage of 100%. In baseline conditions (A2) which were carried out 3 times, a stable percentage of 100% was obtained. Based on the results of the study, it can be concluded that google sites media is effective in improving students' ability to understand science and science learning on the material where living things live for deaf students